Activation response and functional connectivity change in rat cortex after bilateral transcranial direct current stimulation—An exploratory study. Issue 5 (28th January 2021) - Boonzaier, Julia; Straathof, Milou; Ardesch, Dirk Jan; van der Toorn, Annette; van Vliet, Gerard; van Heijningen, Caroline L.; Otte, Willem M.; Dijkhuizen, Rick M.
Abstract: Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique implicated as a promising adjunct therapy to improve motor function through the neuromodulation of brain networks. Particularly bilateral tDCS, which affects both hemispheres, may yield stronger effects on motor learning than unilateral stimulation. Therefore, the aim of this exploratory study was to develop an experimental model for simultaneous magnetic resonance imaging (MRI) and bilateral tDCS in rats, to measure instant and resultant effects of tDCS on network activity and connectivity. Naïve, male Sprague‐Dawley rats were divided into a tDCS ( n  = 7) and sham stimulation group ( n  = 6). Functional MRI data were collected during concurrent bilateral tDCS over the sensorimotor cortex, while resting‐state functional MRI and perfusion MRI were acquired directly before and after stimulation. Bilateral tDCS induced a hemodynamic activation response, reflected by a bilateral increase in blood oxygenation level‐dependent signal in different cortical areas, including the sensorimotor regions. Resting‐state functional connectivity within the cortical sensorimotor network decreased after a first stimulation session but increased after a second session, suggesting an interaction between multiple tDCS sessions. Perfusion MRI revealed no significant changes in cerebral blood flow after tDCS. Our exploratory study demonstrates successful application of an MRI‐compatible bilateral tDCS setup in an animal model. Our results indicate that bilateral tDCS can locally modulate neuronal activity and connectivity, which may underlie its therapeutic potential. Abstract : Our study demonstrates that simultaneous functional magnetic resonance imaging (MRI) and transcranial direct current stimulation (tDCS) in rats is feasible with an MRI‐compatible electrode montage. We found that bilateral tDCS can locally modulate neural activity and functional connectivity in rat brain, while cortical functional connectivity is differentially affected under the tDCS cathode and anode.